2016
DOI: 10.1080/16546628.2017.1264713
|View full text |Cite|
|
Sign up to set email alerts
|

Natural sea salt consumption confers protection against hypertension and kidney damage in Dahl salt-sensitive rats

Abstract: Although sea salts are widely available to consumers nowadays, whether its consumption over refined salt has any real health benefits is largely unknown. This study was conducted to compare hypertension-inducing propensity of natural sea salt (SS) to refined salt (RS) in a well-established animal model of hypertension. Five groups of male Dahl salt-sensitive rats were fed rat chow diet supplemented with various amounts of salt for 15 weeks. The groups were: control (CON, n = 10), 4% RS (RS4), 4% SS (SS4), 8% R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(32 reference statements)
0
11
0
1
Order By: Relevance
“…Although it is generally perceived that a HS diet is usually associated with the induction of higher biomarkers of inflammation, most of these findings are observed in population studies in which HS diets are often coded for subjective food associated with more fat and protein‐rich diets, which could be skewing some of these results (Zhu et al., 2014). An interesting recent study also suggested that consumption of refined salt, but not natural sea‐salt, induces hypertension and cause abnormal kidney pathology in Dahl salt‐sensitive rats (Lee et al., 2017). Thus, there exists a complex relationship between salt intake and immunity development in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally perceived that a HS diet is usually associated with the induction of higher biomarkers of inflammation, most of these findings are observed in population studies in which HS diets are often coded for subjective food associated with more fat and protein‐rich diets, which could be skewing some of these results (Zhu et al., 2014). An interesting recent study also suggested that consumption of refined salt, but not natural sea‐salt, induces hypertension and cause abnormal kidney pathology in Dahl salt‐sensitive rats (Lee et al., 2017). Thus, there exists a complex relationship between salt intake and immunity development in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…; Lee et al . ). Pulmonary oedema and pulmonary vein fibrosis have also been observed in this model, but no catheter‐based haemodynamics have been reported (Doi et al .…”
Section: Definitions Classification Of Subtypes and Diagnostic Factomentioning
confidence: 97%
“…Although their relationship remains controversial, a high salt intake induces hypertension in salt-sensitive persons. It has been reported that different salt types influence metabolic disturbances differently [32]. For example, bamboo and solar salts have less hypertensive effects because they contain higher mineral contents, such as potassium and magnesium [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that different salt types influence metabolic disturbances differently [32]. For example, bamboo and solar salts have less hypertensive effects because they contain higher mineral contents, such as potassium and magnesium [32]. Soy sauce usage instead of salt can potentially lessen metabolic disturbances in estrogen-deficient animals.…”
Section: Discussionmentioning
confidence: 99%